Main contractors' design contribution to the delivery of green buildings - Mothobiso, Charles (My University, 2016)
This study set out to establish the extent to which South African contractors are seen as capable of engaging and contributing towards the designs of green buildings. The study further examines how the traditional procurement path, which is dominant in delivery of construction projects, affects a contractor’s contribution towards green buildings. The problem that exists is the exclusion of contractors at the design stage of a project through the use of the traditional procurement path. This exclusion potentially leads to clients not getting the full benefits of green practices in the delivery of their projects. The research adopted a positivist methodology collecting quantitative data using a questionnaire surveying construction professionals that are registered with the Green Building Council of South Africa (GBCSA).The construction professionals that were surveyed include construction managers, project managers, architects, quantity surveyors and engineers who have direct experience and knowledge of green buildings Findings from the research reveals that there is a perception that the lack of awareness of green buildings in South Africa leads to certain clients, most notably government and parastatals, to invest less in green buildings. The use of the traditional procurement path is perceived to be inappropriate in the delivery of green buildings. This is due to the fact that the traditional procurement path excludes involvement by contractors at the early stages of the project therefore they do not contribute to the design of green buildings. The clients are therefore advised to plan and strategise procurement plans so that contractors can be involved early during the design stages, so that they can provide input so as to improve the buildability of projects and prepare proper health and safety plans.
Thesis is submitted in partial fulfilment for the degree of Master of Science (Building) to the Faculty of Engineering and the Built Environment, School of Construction Economics and Management at the University of the Witwatersrand, Johannesburg, 2016
Keywords: Construction industry--South Africa; Sustainable buildings--Design and construction